Industrial area as a basis for spatial optimization of land use in Kiev - Tsviakh О.; Openko І. (Land Management, Cadastre and Land Monitoring, 2017)
In article deals with problem of using the urban land, including land under the industrial objects in Kiev. Also was analysed the ways of optimization the urban land using. Today become particularly acute the problem for efficient use of urban land use, including land for industrial facilities non-functioning as a reserve future development of Kyiv-based ecological-economic approach to solving them. However, to ensure sustainable development of urban population (preserve and improve health, improve working conditions, improve living conditions, increase the construction of social and affordable housing, reducing unemployment, creating new jobs, improving the ecological state of the environment) within large cities , you need to identify ways to optimize existing urban land use. The complexity of management decisions is determined, above all, the fact that in most cities of Ukraine territorial resources are exhausted and vacant land plots require significant investment. Also, a significant proportion of non-functioning industrial enterprises, which occupy large areas in the city were in Kyiv surrounded by residential development, buffer zones, technogenic disturbed and contaminated land. These objects be removed outside the settlements and the land on which they are to be re-cultivated and restoration for more ecological, economically feasible and sustainable use. The rapid development of large cities around the world and increase their impact on the environment and society is accompanied by a set ekonominyh, environmental and social issues that significantly influence the development of land relations in settlements in general. Today in Kyiv observed the changing dynamics of land area, which is to reduce the share of agricultural and forestry purposes and to increase the territory of other categories. The process of de-industrialization and suburbanization of urban land use is inevitable. They in turn accelerate other processes - "crowding out" of industrial facilities in the cities suburbs, which in turn will foster a number of ecological, economic and social problems. Management processes of territorial development of the city can be successful only when decisions on current issues of land use based on strategic, long-term development programs, offensive planning ideas zemleohoronnyh ensure consistency of implementation measures. Optimization of territorial development. Kyiv is to improve the structure of the land to improve the efficiency and usage of urban land, improvement of investment attractiveness, increase their profitability, ensuring the sustainability of ecosystems city. In our belief improving ecological and economic situation of the city, forming an effective urban land may provide by moving industrial facilities beyond Kyiv, to reorganize these areas of balance and formation of the optimal structure of urban land. Given the shortage of available areas for further development of the city’s new housing construction, facilities service sector, tourism, etc. Industrial areas in which rolled production function, should be seen as a spatial basis optimize land use in Kiev. Taking into account the economic, social and environmental factors optimizing industrial areas are not functioning businesses that occupy large areas of urban land should also consider the most expedient type of land use. This, in turn, will contribute to the growth of urban land use, improve the well-being of the urban population, increasing tax revenues to the city budget, city economic development and is a prerequisite for creating favorable conditions for attracting investments. Keywords: urbanization, deindustrialization, industrial objects, industrial area, urban land use, land resources.